METAPHORS AND METONYMIES FOR ANGER IN THE OLD TESTAMENT: A COGNITIVE LINGUISTIC APPROACH - Kotzé, Zacharias (Scriptura, 2005)
This article emphasises the need of a cognitive linguistic approach to the study of the emotion of anger in the Old Testament. Most of the works to date have reduced the concept of wrath to a just principle of retribution. The detailed Classical Hebrew language of anger, however, reveals important aspects of the ancient Israelite conceptualisation of this emotion that cannot be fitted into such an abbreviated view. The ideal cognitive model of anger as construed by the ancient Israelites, was motivated by cultural, environmental and experiential factors, such as bodily changes associated with the emotion, aspects of the nonverbal communication of anger, the ancient Israelite theory of humours and Palestinian fauna and meteorology.